(3GdeNJGQ ef SbW GdRfOs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3CYf hNP GdbdGU cTaJ MGdkG hef YfO GdXdGe WdHJ eGdG s
(3BNQgG (B:s
(3EPG LGhQJgG fHPJ LhGQi hEdG Jda di PfHkG JLfg JeJ GdeNJGQGJ ef SbW GdRfO , dCHi GdYdGA GdeYQi , hgj Cda heGFI HjJ hHjJ hGMO , hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3COH (B34) s
Keywords: (3GdCOHs